2021
DOI: 10.1177/13670069211018842
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of lexical processing in monolinguals and bilinguals

Abstract: Aims and objectives: This study aims to investigate how lexical processing (LP) is organized in early Turkish–English bilinguals and Turkish monolinguals. Methodology: We used a visual hemifield paradigm where bilingual ( n = 48) and monolingual ( n = 53) participants performed a lexical decision task. Bilingual participants performed the task in both their languages. Data and analysis: We recorded response times (RTs) and the accuracy rates (ARs) of the participants. An analysis of variance and t-test were ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In a brain imaging study, Chen et al (2015) found greater activation in the left hemisphere for L2 than for L1 emotion words, and associated this result with the greater need for cognitive and attentional resources entailed by L2. In simultaneous bilinguals, on the other hand, bilateral representation of both languages has been reported (Kuruoglu & Mergen 2016, Mergen & Kuruoglu 2021).…”
Section: Brain Representations Of Emotion Wordsmentioning
confidence: 99%
“…In a brain imaging study, Chen et al (2015) found greater activation in the left hemisphere for L2 than for L1 emotion words, and associated this result with the greater need for cognitive and attentional resources entailed by L2. In simultaneous bilinguals, on the other hand, bilateral representation of both languages has been reported (Kuruoglu & Mergen 2016, Mergen & Kuruoglu 2021).…”
Section: Brain Representations Of Emotion Wordsmentioning
confidence: 99%